The Dispute Settlement over the Ownership of a Double Certificates in Cirebon District Land Office - Bayu Nuraulia; I Nengah Sugiarta; Djauhari Djauhari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
Birth of the Law of the Republic of Indonesia Number 5 of 1960 on Basic Regulation of Agrarian (BAL) has brought about significant changes in the world Indonesian land. BAL and a set of implementation regulations are expected to provide legal guarantees for the rights holders on the ground. But in fact the land can not be separated from problems, one of which occurred in Cirebon is the emergence of multiple certificate which led to the dispute. Here will be explained the factors that led to the emergence of a double and a certificate of completion method of dispute. To the authors do research with sociological juridical approach that combines literary and legal material facts obtained in the field through interviews. From these studies obtained answers that the emergence of double certificates can occur due to external factors and internal factors. For that matter, BPN trying to find a way out with the mediation. But if it does not receive the meeting point, the parties can file a lawsuit in court.Keywords: Dispute; Double certificates.